1964
DOI: 10.1128/jb.87.1.220-225.1964
|View full text |Cite
|
Sign up to set email alerts
|

GROWTH OF ACANTHAMOEBA CASTELLANI WITH THE YEAST TORULOPSIS FAMATA

Abstract: Acanthamoeba castellani and Torulopsis famata cells were cultured together for 10 days at three different temperatures: 18, 25, and 32 C. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 1 publication
(2 reference statements)
1
7
0
Order By: Relevance
“…[21], providing an early report of fungal–amoeba interactions whereby the amoeba appear to lyse the yeast cells. In 1955, A. castellanii was shown to feed on C. neoformans [22] and subsequently demonstrated to feed on cultures of Torula famata and Candida parapsilosis [23]. Interestingly, this early study reported that growth on the yeast C. parapsilosis was much faster than growth on the filamentous T. famata since the protozoa had difficulty ingesting hyphae [23].…”
Section: Early Studies On the Interaction Of Fungi And Amoebamentioning
confidence: 99%
See 2 more Smart Citations
“…[21], providing an early report of fungal–amoeba interactions whereby the amoeba appear to lyse the yeast cells. In 1955, A. castellanii was shown to feed on C. neoformans [22] and subsequently demonstrated to feed on cultures of Torula famata and Candida parapsilosis [23]. Interestingly, this early study reported that growth on the yeast C. parapsilosis was much faster than growth on the filamentous T. famata since the protozoa had difficulty ingesting hyphae [23].…”
Section: Early Studies On the Interaction Of Fungi And Amoebamentioning
confidence: 99%
“…In 1955, A. castellanii was shown to feed on C. neoformans [22] and subsequently demonstrated to feed on cultures of Torula famata and Candida parapsilosis [23]. Interestingly, this early study reported that growth on the yeast C. parapsilosis was much faster than growth on the filamentous T. famata since the protozoa had difficulty ingesting hyphae [23]. Beginning in the late 1970s, Bulmer and colleagues carried out studies of the interaction of C. neoformans with amoeba and established that the protozoa preyed and devoured encapsulated cells with the emergence of hyphal cells as resistant forms, which were hypovirulent in mice [24,25].…”
Section: Early Studies On the Interaction Of Fungi And Amoebamentioning
confidence: 99%
See 1 more Smart Citation
“…All 19 species of yeasts were eaten by at least two of the amoebae and all four species of amoebae grew well on several of the yeasts. Nero et al [85] found Acanthamoeba castellanii to grow well on the yeast Torulopsis famata.…”
Section: Phagotrophic Feedingmentioning
confidence: 99%
“…Various bacteria can serve as nutrients for amoebae. The soil amoebae, Acanthamoeba castellani and Acanthamoeba sp., have been shown to grow on both bacteria and yeasts (9,10,11). Chang (4) demonstrated that gram-negative bacilli were utilized by a strain of H. glebae and gram-positive bacilli were not utilized by this organism.…”
Section: Discussionmentioning
confidence: 99%